Development of historical thinking in the first year of high school: analysis of the activities in the History textbook - Nasimba-Mera, Erika (2025)
The limited development of historical thinking among students represents a central problem in the teaching of history, as it restricts their ability to critically interpret the past and move beyond the mere accumulation of information. Given this situation, the present study aims to analyze the extent to which the activities in the first-year high school history textbook contribute to the development of historical thinking among students. To this end, the 121 activities in the textbook were examined according to the type of historical concept, cognitive demand, and type of activity. A mixed approach and content analysis technique were used, employing a code book and analysis sheet as instruments. The information was processed using frequency tables, contingency tables, and a word cloud, with the SPSS and MAXQDA programs. The results highlight that activities related to first-order concepts and with low and intermediate cognitive demands predominate, which highlights the need to diversify the activities in textbooks, incorporating approaches that encourage critical analysis, interpretation, and the reflective use of historical knowledge.